2015
DOI: 10.1002/jhm.2511
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalists caring for patients with advanced cancer: An experience‐based guide

Abstract: Every year, nearly five million adults with cancer are hospitalized. Limited evidence suggests that hospitalization of the cancer patient is associated with adverse morbidity and mortality. Hospitalization of the patient with advanced cancer allows for an intense examination of health status in the face of terminal illness and an opportunity for defining goals of care. This experience-based guide reports what is currently known about the topic and outlines a systematic approach to maximizing opportunities, imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…These results highlight the need for financial education and conversations about the cost of cancer care. Previous quantitative studies also found similar results that 60%‐80% cancer survivors report a desire to discuss out‐of‐pocket and total costs . In addition to discussing direct medical costs, we found that cancer survivors have a number of unmet needs for managing FT, including treatment and supportive information as well as other practical needs.…”
Section: Discussionsupporting
confidence: 82%
“…These results highlight the need for financial education and conversations about the cost of cancer care. Previous quantitative studies also found similar results that 60%‐80% cancer survivors report a desire to discuss out‐of‐pocket and total costs . In addition to discussing direct medical costs, we found that cancer survivors have a number of unmet needs for managing FT, including treatment and supportive information as well as other practical needs.…”
Section: Discussionsupporting
confidence: 82%
“…Providers, including medical, surgical, and radiation oncologists, have a critical role to address financial toxicity as the primary advisor to patients. Sixty to 80% of patients report a desire to discuss cost (both OOP and total cost), 75% of physicians feel responsible to discuss cost, but only 28% of physicians feel comfortable doing this . In one study of metastatic patients with cancer, only 28% had discussed costs with their doctor .…”
Section: Strategies To Reduce Financial Toxicitymentioning
confidence: 99%
“…Difficulty with prognosticating also makes it challenging for acute care clinicians to provide goal‐concordant care to patients with emergent surgical hospitalizations. In these situations, a structured communication approach can help to personalize surgical care delivery to the individual goals of each patient . When prognosis is uncertain and the benefit of proposed interventions is unclear, offering a time‐limited trial of intensive or aggressive care may also offer clinicians, patients, and surrogates an opportunity to evaluate whether proposed therapies are aligned or discordant with the patient’s preferences .…”
Section: Ethical Considerations In Emergent Surgical Hospitalizationsmentioning
confidence: 99%
“…In these situations, a structured communication approach can help to personalize surgical care delivery to the individual goals of each patient. 17,18 When prognosis is uncertain and the benefit of proposed interventions is unclear, offering a time-limited trial of intensive or aggressive care may also offer clinicians, patients, and surrogates an opportunity to evaluate whether proposed therapies are aligned or discordant with the patient's preferences. 19 Surgery may be aligned with the patient's goals at the outset; however, the clinical course may be dynamic, and in cases where postoperative treatment is ineffective or too burdensome, a shift toward comfort-focused care may be more appropriate.…”
Section: Ethical Considerations In Emergent Surgical Hospitalizationsmentioning
confidence: 99%